The role of donor-speciﬁ c anti-HLA antibodies in the development of humoral rejection - L. K. Tkhatl'; I. A. Pashkova; E. D. Kosmacheva (Трансплантология (Москва), 2018)
Humoral rejection belongs to severe complications of the post-transplant period. Mechanisms of humoral rejection proceed through antibody formation. Donor specific anti-HLA antibodies (anti-HLA DSAs) damage transplant tissues by activating the complement system, leading to the dysfunction and loss of the transplanted organ. This article describes the clinical case of humoral rejection development with the identification of anti-HLA DSAs, their impact on the risk of coronary artery disease of the transplanted heart, and the graft loss.